Windows and Linux Penetration Testing from Scratch Harness the power of pen testing with Kali Linux for unbeatable hard-hitting results - Bramwell, Phil; Bramwell, Phil (Packt Publishing, 2022)
Master the art of identifying and exploiting vulnerabilities with Metasploit, Empire, PowerShell, and Python, turning Kali Linux into your fighter cockpitKey FeaturesMap your client's attack surface with Kali LinuxDiscover the craft of shellcode injection and managing multiple compromises in the environmentUnderstand both the attacker and the defender mindsetBook DescriptionLet's be honest$1 (Bsecurity testing can get repetitive. If you're ready to break out of the routine and embrace the art of penetration testing, this book will help you to distinguish yourself to your clients. This pen testing book is your guide to learning advanced techniques to attack Windows and Linux environments from the indispensable platform, Kali Linux. You'll work through core network hacking concepts and advanced exploitation techniques that leverage both technical and human factors to maximize success. You'll also explore how to leverage public resources to learn more about your target, discover potential targets, analyze them, and gain a foothold using a variety of exploitation techniques while dodging defenses like antivirus and firewalls. The book focuses on leveraging target resources, such as PowerShell, to execute powerful and difficult-to-detect attacks. Along the way, you'll enjoy reading about how these methods work so that you walk away with the necessary knowledge to explain your findings to clients from all backgrounds. Wrapping up with post-exploitation strategies, you'll be able to go deeper and keep your access. By the end of this book, you'll be well-versed in identifying vulnerabilities within your clients' environments and providing the necessary insight for proper remediation.What you will learnGet to know advanced pen testing techniques with Kali LinuxGain an understanding of Kali Linux tools and methods from behind the scenesGet to grips with the exploitation of Windows and Linux clients and serversUnderstand advanced Windows concepts and protection and bypass them with Kali and living-off-the-land methodsGet the hang of sophisticated attack frameworks such as Metasploit and EmpireBecome adept in generating and analyzing shellcodeBuild and tweak attack scripts and modulesWho this book is forThis book is for penetration testers, information technology professionals, cybersecurity professionals and students, and individuals breaking into a pentesting role after demonstrating advanced skills in boot camps. Prior experience with Windows, Linux, and networking is necessary.s